2011
DOI: 10.1161/atvbaha.110.219501
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine Derived From ADP Can Contribute to Inhibition of Platelet Aggregation in the Presence of a P2Y 12 Antagonist

Abstract: Objective-To investigate whether adenosine diphosphate (ADP)-derived adenosine might inhibit platelet aggregation, especially in the presence of a P2Y 12 antagonist, where the effects of ADP at the P2Y 12 receptor would be prevented. Methods and Results-Platelet aggregation was measured in response to thrombin receptor activator peptide by platelet counting in platelet-rich plasma (PRP) and whole blood in the presence of ADP and the P2Y 12 antagonists cangrelor, prasugrel active metabolite, and ticagrelor. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 43 publications
(67 reference statements)
0
20
1
Order By: Relevance
“…Our results are in disagreement with a previous report by Iy u et al [25], in which dipyridamole, but not ticagrelor, potentiated the inhibitory effect of exogenous adenosine on platelet aggregation. There are many methodological differences including the method to measure platelet aggregation in whole blood (Multiplate vs. single platelet counting), the type of platelet agonist (collagen vs. thrombin receptor activating peptide) and the observa- figure).…”
Section: Discussioncontrasting
confidence: 99%
“…Our results are in disagreement with a previous report by Iy u et al [25], in which dipyridamole, but not ticagrelor, potentiated the inhibitory effect of exogenous adenosine on platelet aggregation. There are many methodological differences including the method to measure platelet aggregation in whole blood (Multiplate vs. single platelet counting), the type of platelet agonist (collagen vs. thrombin receptor activating peptide) and the observa- figure).…”
Section: Discussioncontrasting
confidence: 99%
“…However, in the presence of dipyridamole, an inhibitor of ENT [34][35][36][37], both adenosine and ADP brought about inhibition of platelet function as in PRP. That adenosine is indeed the mediator of inhibition of platelet function was confirmed using ADA which prevented the inhibitory effects of adenosine and ADP [29]. In the experiments described here, we looked at the potency of adenosine acting as an inhibitor of platelet aggregation in whole blood containing dipyridamole, and showed that in the presence of a P2Y 12 antagonist that potency was increased in the same way as for the prostaglandins that we investigated.…”
Section: Discussionmentioning
confidence: 66%
“…In a previous publication [29], we have already shown that P2Y 12 antagonists enhance the inhibitory effects of adenosine. Indeed, concentration-dependent inhibition of platelet function was also seen with ADP in the presence of a P2Y 12 antagonist consequent to conversion of the ADP to adenosine.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Additionally, PA in MEA takes place on surface similar with ruptured plaques or vascular injury [7]. However, if MEA used whole blood drawn from patients on ticagrelor or phosphodiesterase inhibitor, the plasma adenosine is rapidly taken up by erythrocytes in whole blood, and this ex vivo measurement can underestimate the actual in vivo antiplatelet effect of these agents [26]. Moreover, the results of MEA-based studies predicting the risk of clinical events were contradictory: some studies provided good predictive values [11][12][13], but some did not [14,27].…”
mentioning
confidence: 99%